Tradutor de arquivos MIDI para texto utilizando linguagem funcional CLEAN - Machado, André Campos (2001)
One of the greatest challenges of the present research involving the manipulation of MIDI SMF archives is the lack of specific instructional material, as in the description of the MIDI protocol, as for a computing system, which bears an adherent music language on the musical paradigm. The present work was developed with the objective to contribute to solve that need, creating instructing tools for the manipulation of MIDI archives using the a functional language CLEAN, which shows itself enough adherent on to the musical paradigm. Another choice factor for the present language took into account its great deal of speed and efficiency in the manipulation of the lists, as to the use of the main basic tools and as to the use of the Zermelo-Frankel notation. The system, makes available all the basic reading tools of the standard MIDI archives and produces, as a final product, a text archive which contains all information found in the recorded music